A new smoking cessation 'cascade' among women with or at risk for HIV infection. (1st January 2022) - Breger, Tiffany L.; Westreich, Daniel; Edmonds, Andrew; Edwards, Jessie K.; Zalla, Lauren C.; Cole, Stephen R.; Ramirez, Catalina; Ofotokun, Igho; Kassaye, Seble G.; Brown, Todd T.; Konkle-Parker, Deborah; Jones, Deborah L.; et al.
Abstract : Objectives: The aim of this study was to define a smoking cessation 'cascade' among USA women with and without HIV and examine differences by sociodemographic characteristics. Design: An observational cohort study using data from smokers participating in the Women's Interagency HIV Study between 2014 and 2019. Methods: We followed 1165 women smokers with and without HIV from their first study visit in 2014 or 2015 until an attempt to quit smoking within approximately 3 years of follow-up, initial cessation (i.e. no restarting smoking within approximately 6 months of a quit attempt), and sustained cessation (i.e. no restarting smoking within approximately 12 months of a quit attempt). Using the Aalen-Johansen estimator, we estimated the cumulative probability of achieving each step, accounting for the competing risk of death. Results: Forty-five percent of smokers attempted to quit, 27% achieved initial cessation, and 14% achieved sustained cessation with no differences by HIV status. Women with some post-high school education were more likely to achieve each step than those with less education. Outcomes did not differ by race. Thirty-six percent [95% confidence interval (95% CI): 31–42] of uninsured women attempted to quit compared with 47% (95% CI: 44–50) with Medicaid and 49% (95% CI: 41–59) with private insurance. Conclusion: To decrease smoking among USA women with and without HIV, targeted, multistage interventions, and increased insurance coverage are needed to address shortfalls along this cascade. Abstract : Supplemental Digital Content is available in the text